PERKEMBANGAN KOGNITIF ANAK DAN REMAJA DI TENGAH POPULARITAS APLIKASI TIK TOK: Studi Selebgram Tiktokers Remaja Kota Pontianak - Sopian - Lubis (Raheema, 2021)
Tiktok's popularity is motivated by the rapid technology and the internet needs of the people who have become basic necessities, Tiktok's presence is used creatively by some teenagers so that he makes himself a famous person. In Pontianak, many celebrities use the Tiktok application as their Instagram content. The short video application has positive and negative impacts on the cognitive development of children and adolescents, this is the background of the authors to raise this research, the method used is qualitative with a cognitive psychology approach, the research subject is Tiktok selebgram chosen by the author based on several aspects including its popularity in Pontianak and researchers conducted interviews and analyzed and developed through theories of cognitive development of children and adolescents, the results of the study showed the popularity of Tiktok provides a cognitive impact on children and adolescents so that it can affect various cognitive aspects of children and adolescents. Keywords: Cognitive, Popularity, Selebgram, Tiktok